2018
DOI: 10.1111/pce.13460
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin regulation in roots controls plant hydraulic conductance, stomatal conductance, and leaf water potential in Pinus radiata under water stress

Abstract: Stomatal regulation is crucial for forest species performance and survival on drought‐prone sites. We investigated the regulation of root and shoot hydraulics in three Pinus radiata clones exposed to drought stress and its coordination with stomatal conductance (gs) and leaf water potential (Ψleaf). All clones experienced a substantial decrease in root‐specific root hydraulic conductance (Kroot‐r) in response to the water stress, but leaf‐specific shoot hydraulic conductance (Kshoot‐l) did not change in any of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 77 publications
(111 reference statements)
6
34
0
2
Order By: Relevance
“…Control plants were irrigated with 2 liters of water twice per week, which was enough to saturate the substrate. For the drought treatment, plants were never irrigated from the start until the end of the experiment (Rodriguez-Gamir et al, 2019). Flooding and flooding plus salinity was imposed by submerging the seedlings to the root-collar (3 cm above the surface) without draining the pots (Pezeshki, 1992).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Control plants were irrigated with 2 liters of water twice per week, which was enough to saturate the substrate. For the drought treatment, plants were never irrigated from the start until the end of the experiment (Rodriguez-Gamir et al, 2019). Flooding and flooding plus salinity was imposed by submerging the seedlings to the root-collar (3 cm above the surface) without draining the pots (Pezeshki, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…mercuric chloride or hydroxyl radicals) demonstrated that AQP down-regulation is the principal cause of alterations of the radial pathway, resulting in a decrease in K root (Ehlert et al, 2009; Knifer and Fricke, 2011; Maurel and Nacry 2020). Despite a recent flurry of studies, compared to reference plants used in molecular studies such as corn, tobacco and Arabidopsis (Siefritz et al, 2002; Lopez et al, 2003; Bramley et al, 2009; Sade et al, 2010; Tan and Zwiazek, 2019), the importance of species differences in AQP regulation in woody plants and its effect within the SPAC is still poorly understood (McElrone et al, 2007; Gambetta et al, 2013; Johnson et al, 2014; Rodriguez-Gamir et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Усложним модель, используя качественную информацию о моделируемом объекте: знание об устьичной природе регуляции потока водяного пара [18,19]. В простейшем случае, когда температура хвои близка к температуре воздуха, поток водяного пара (E) из растения в атмосферу определяется по формуле [20]:…”
Section: учет устьичной проводимостиunclassified
“…Функции, определяющие динамику воды: устьичная проводимость (Ust) как функция радиации (Q) и дефицита упругости водяного пара (VPD), функция регулирования устьичной проводимости стволе (Reg) в зависимости от дефицита воды в стволе (WD), функция скорости поступление воды из почвы (FWF) в зависимости от дефицита воды в стволе (WD). Построенная в итоге модель соответствует современным представлениям о регуляции влаги в растении [10][11][12][13][14][15][16][17][18][19][20]22], она показала хорошее качественное совпадение с независимыми экспериментальными данными.…”
Section: динамическая модель Ust(qvpd)•reg(wd)andfwf(wd)unclassified
“…Another central question in woody plant hydraulics is the role of the roots in determining whole‐plant water transport capacity. Hydraulic failure below ground can determine a species' vulnerability to drought (Johnson et al, ), and one of the studies in this issue reports a role for root aquaporins in regulating whole‐plant water transport, stomatal conductance, and leaf water status (Rodríguez‐Gamir et al, ).…”
mentioning
confidence: 99%